2007
DOI: 10.1038/sj.ejcn.1602899
|View full text |Cite
|
Sign up to set email alerts
|

Serum testosterone and urinary excretion of steroid hormone metabolites after administration of a high-dose zinc supplement

Abstract: Objectives: To investigate whether the administration of the zinc-containing nutritional supplement ZMA causes an increase of serum testosterone levels, which is an often claimed effect in advertising for such products; to monitor the urinary excretion of testosterone and selected steroid hormone metabolites to detect potential changes in the excretion patterns of ZMA users. Subjects: Fourteen healthy, regularly exercising men aged 22-33 years with a baseline zinc intake between 11.9 and 23.2 mg day À1 prior t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 21 publications
0
16
1
1
Order By: Relevance
“…Kilic concluded that "administration of a physiologic dose of zinc can be beneficial to performance." Contradictory, Koehler et al [40] noted that zinc supplementation may reverse lowered testosterone levels and restore disturbed testosterone metabolism in cases of mild or severe zinc deficiency; it is not capable of further increasing serum testosterone when sufficient zinc is provided by the regular diet. The disparity in results in the aforementioned studies with our findings might be due to variations in the consumed dose of zinc supplement, status of zinc in subjects, amount of zinc intake on diet, as well as the improper time duration for the effect of supplementation does in our study.…”
Section: Discussionmentioning
confidence: 97%
“…Kilic concluded that "administration of a physiologic dose of zinc can be beneficial to performance." Contradictory, Koehler et al [40] noted that zinc supplementation may reverse lowered testosterone levels and restore disturbed testosterone metabolism in cases of mild or severe zinc deficiency; it is not capable of further increasing serum testosterone when sufficient zinc is provided by the regular diet. The disparity in results in the aforementioned studies with our findings might be due to variations in the consumed dose of zinc supplement, status of zinc in subjects, amount of zinc intake on diet, as well as the improper time duration for the effect of supplementation does in our study.…”
Section: Discussionmentioning
confidence: 97%
“…Zn deficiency enhances apoptotic processes in the testis and negatively affects semen quality by reducing the number and motility of sperm (Kumari et al 2011). Research conducted by Koehler et al (2009) does not show a statistically significant increase in the concentration of TT and FT in young men supplemented with Zn (Koehler et al 2009). Jalali et al (2010) demonstrate that Zn supplementation of male hemodialysis patients results in increased concentrations of luteinizing hormone and testosterone.…”
Section: Bioelementsmentioning
confidence: 91%
“…Wilborn et al 23 showed that 8 weeks of ZMA supplementation, combined with resistance training, resulted in no significant differences in the plasma concentrations of Zn or magnesium in anabolic (T, IGF-1 and GH) or catabolic hormones (cortisol), gains in muscle mass and strength or cycling anaerobic capacity when compared to placebo. Koehler et al 24 also reported, in a well-controlled study, that 56 days of ZMA supplementation in physically active males did not alter plasma total T, free T or urinary excretion of T metabolites.…”
Section: Zinc Monomethionine Aspartatementioning
confidence: 93%